SUSTAINABILITY PRACTICES AND COMPETITIVE ADVANTAGE IN INDONESIAN CONSUMER GOODS COMPANIES - Ijang Faisal; Herry Achmad Buchory; Uce Karna Suganda (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Environmental concerns and stakeholder pressures drive Indonesian consumer goods companies to adopt sustainability practices, yet implementation varies substantially across organizations. Aims: This study examines sustainability practice adoption and its relationship with competitive advantage in Indonesian consumer goods sector. Research Method: Mixed-methods research combining survey of 142 consumer goods companies with case studies of 10 sustainability leaders across food, beverage, personal care, and household products categories. Results and Conclusion: Companies implementing comprehensive sustainability strategies demonstrate 27 percent stronger brand reputation, 23 percent improved customer loyalty, and 31 percent better investor attractiveness compared to minimal adopters. However, only 34 percent of companies integrate sustainability into core strategy. Green product development, waste reduction, and sustainable sourcing emerge as most impactful practices. Contribution: Research provides framework for Indonesian consumer goods companies to develop sustainability strategies generating competitive advantages while addressing environmental and social responsibilities.